2020
DOI: 10.1177/2380084420952747
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Pregnant Dental and Health Care Workers amid COVID-19

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a highly contagious disease that quickly reached pandemic levels. Over 5 million COVID-19 cases and approximately 330,000 deaths have been recorded worldwide. Transmission is primarily spread through direct, indirect (through contaminated objects or surfaces), or close contact with infected people via respiratory droplets, the mouth, and/or nose secretions. Health care professionals (HCPs), including dental HCPs, are recognized to be at considerably high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Findings point to a number of important recommendations to better support women healthcare workers, including workplace mental health support, economic assistance to counteract widening pay gaps, and strategies to support families in their caregiving duties ( Jones et al 2020 ; Mann et al 2020 ; Mercer et al 2014 ; Samouei et al 2019 ). Additionally, strategies that support and advance women's careers and increase women's representation in leadership are an important way to combat gender-blindness in healthcare systems and ensure that the needs of women healthcare workers are addressed during the COVID-19 pandemic and in future health crises ( van Daalen et al 2020 ; Jones et al 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Findings point to a number of important recommendations to better support women healthcare workers, including workplace mental health support, economic assistance to counteract widening pay gaps, and strategies to support families in their caregiving duties ( Jones et al 2020 ; Mann et al 2020 ; Mercer et al 2014 ; Samouei et al 2019 ). Additionally, strategies that support and advance women's careers and increase women's representation in leadership are an important way to combat gender-blindness in healthcare systems and ensure that the needs of women healthcare workers are addressed during the COVID-19 pandemic and in future health crises ( van Daalen et al 2020 ; Jones et al 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that healthcare workers (HCWs) were one of the most exposed groups to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during the coronavirus disease 2019 (COVID-19) pandemic due to the nature of their work and their role in containing the pandemic ( 1 , 2 , 3 , 4 ). Considering that pregnant women are more susceptible to infections ( 5 ) and develop severe clinical forms of the disease ( 6 ), several organisations and health and safety at work experts ( 1 , 7 , 8 , 9 , 10 ) suggested that pregnant HCWs should stop working with patients with suspected or proven SARS-CoV-2 infection, but there is little information about pregnant HCWs and their challenges with exposure to SARS-CoV-2 at the workplace during the pandemic.…”
mentioning
confidence: 99%